Motif Khas Magetan: Identitas Lokal dalam Inovasi Produk Tas Kulit - Agung Wicaksono; Yonata Buyung Mahendra; Tri Wulandari; Risky Kurniawan (Corak, 2025)
Magetan Regency is known as one of the leading leather tanning industry centers in Indonesia. This industry has supplied leather materials for various products such as shoes, bags, and accessories for many years. However, the locally produced leather products have yet to display a distinctive Magetan identity in their visual design. Generally, product designs tend to follow market trends without considering the reinforcement of local cultural values. In fact, in today’s global design trends, local wisdom has become an essential asset in product innovation and branding strategies. The competition in the leather product market, both locally and internationally, demands differentiation not only in terms of quality and function but also through strong narrative and distinctive visual identity.The development of culturally inspired motifs from Magetan holds great potential to create added value, strengthen regional identity, and open up new marketing opportunities. Unfortunately, design approaches based on local wisdom within Magetan’s leather industry remain limited. The visual potential of batik art, carved ornaments, or regional symbols has not been widely utilized by UMKMs or designers.This applied research aims to design and develop distinctive motifs representing Magetan Regency that can be applied to leather product designs, particularly women’s handbags. The selection of the women’s handbag segment is based on the dominant female consumer market in the leather goods industry. Design innovation will be carried out through pattern-making, engraving, and decorative stitching techniques, allowing for the aesthetic and functional visualization of motifs.The research method combines qualitative exploratory and experimental approaches. The research stages include: (1) visual study of Magetan’s culture and traditional motifs; (2) identification of applicable motif potentials for leather product design; (3) design experimentation and prototype development of women’s handbags; and (4) product evaluation through user response testing to assess attractiveness, functionality, and representation of local identity.The design process consists of several phases: pre-design, design, realization, and presentation. The practice-led research method is applied to maximize outcomes that can also be comprehended by potential producers.Abstrak Kabupaten Magetan dikenal sebagai salah satu sentra industri penyamakan kulit terkemuka di Indonesia. Industri ini telah memasok bahan kulit untuk beragam produk seperti sepatu, tas, dan aksesori selama bertahun-tahun. Namun, produk kulit hasil olahan industri lokal masih belum menunjukkan identitas khas Magetan secara visual. Umumnya, desain produk cenderung mengikuti tren pasar tanpa mempertimbangkan penguatan nilai budaya lokal. Padahal, pada tren desain global saat ini, local wisdom justru menjadi aset penting dalam inovasi produk dan strategi branding. Persaingan pasar produk kulit, baik di tingkat lokal maupun internasional, menuntut diferensiasi yang tidak hanya dari sisi kualitas dan fungsi, tetapi juga dari kekuatan narasi dan ciri khas visual. Pengembangan motif berbasis budaya lokal Magetan memiliki potensi besar untuk menciptakan nilai tambah, memperkuat identitas daerah, serta membuka peluang pemasaran baru. Kamingnya, hingga kini pendekatan desain berbasis kearifan lokal dalam industri kulit Magetan masih minim. Potensi visual dari seni batik, ornamen ukiran, atau simbol-simbol khas daerah belum banyak dimanfaatkan oleh pelaku UMKM maupun desainer. Penelitian terapan ini bertujuan untuk merancang dan mengembangkan motif khas Kabupaten Magetan yang dapat diaplikasikan pada desain produk kulit, khususnya tas wanita.Pemilihan segmen tas wanita didasarkan pada dominasi pasar konsumen perempuan dalam industri produk kulit. Inovasi desain akan dilakukan melalui teknik pemolaan, ukiran, hingga jahit hias yang memungkinkan visualisasi motif secara estetis dan fungsional. Metode yang digunakan dalam penelitian ini adalah gabungan antara pendekatan kualitatif eksploratif dan eksperimental. Tahapan penelitian meliputi: (1) studi visual terhadap budaya dan motif khas Magetan; (2) identifikasi potensi motif yang aplikatif untuk desain produk kulit; (3) eksperimen desain dan perancangan purwarupa tas wanita; serta (4) evaluasi produk melalui uji respon pengguna untuk menilai aspek daya tarik, fungsi, dan representasi identitas lokal. Tahapan perancangan dimulai dari tahapan pra perancangan, perancangan, perwujudan karya, penyajian. Metode practice led research digunakan untuk memaksimalkan hasil yang juga dapat dimengerti oleh calon produsennya.